2008
DOI: 10.1016/j.molcel.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-Selective Enrichment Enables Quantitative Phosphoproteomics of the Kinome across the Cell Cycle

Abstract: Protein kinases are pivotal regulators of cell signaling that modulate each other's functions and activities through site-specific phosphorylation events. These key regulatory modifications have not been studied comprehensively, because low cellular abundance of kinases has resulted in their underrepresentation in previous phosphoproteome studies. Here, we combine kinase-selective affinity purification with quantitative mass spectrometry to analyze the cell-cycle regulation of protein kinases. This proteomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
468
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(508 citation statements)
references
References 43 publications
32
468
0
8
Order By: Relevance
“…Multiple large-scale proteomic analyses have indicated that Cdc7 is phosphorylated at Ser16, Ser302, and Thr503 in prometaphase, [26][27][28] which is consistent with our prediction (Fig 1E.). To further confirm it, we determined the extent of hyper-phosphorylation in vivo by two-dimensional PAGE with mycFLAGtagged Cdc7 WT and Cdc7 £5A expressed in HEK293T cells.…”
Section: Cdc7 Is Phosphorylated During Prometaphase In a Cdk1-dependesupporting
confidence: 92%
See 1 more Smart Citation
“…Multiple large-scale proteomic analyses have indicated that Cdc7 is phosphorylated at Ser16, Ser302, and Thr503 in prometaphase, [26][27][28] which is consistent with our prediction (Fig 1E.). To further confirm it, we determined the extent of hyper-phosphorylation in vivo by two-dimensional PAGE with mycFLAGtagged Cdc7 WT and Cdc7 £5A expressed in HEK293T cells.…”
Section: Cdc7 Is Phosphorylated During Prometaphase In a Cdk1-dependesupporting
confidence: 92%
“…This may be due to Cdc7 autophosphorylation 14 or phosphorylation by other kinases such as polo-like kinase (Plk), as large scale proteomics studies indicated that Plk phosphorylates Cdc7 at Serine 27 and 277 in prometaphase. 26,28,[30][31][32][33] In any event, our data demonstrate that Cdc7 is phosphorylated at multiple sites in a mitotic Cdkdependent manner around prometaphase.…”
Section: Cdc7 Is Phosphorylated During Prometaphase In a Cdk1-dependementioning
confidence: 62%
“…In some cases, definitive localization of the phosphorylation site could not be obtained (Figure 1a, sites marked in green). Some of these sites have previously been reported, including Ser21 and Ser1177, which have been identified in different largescale analyses of phosphoproteins (Beausoleil et al, 2004;Dai et al, 2007;Cantin et al, 2008;Daub et al, 2008;Dephoure et al, 2008;Zanivan et al, 2008). In addition, the phosphopeptides containing Ser1174, Ser1219, Thr1222, Thr1295, Ser1385, Tyr1386 and Ser1388, which have recently reported been, were also detected (Dephoure et al, 2008;Zanivan et al, 2008).…”
Section: Identification Of Phosphorylation Sites Within Rictormentioning
confidence: 70%
“…The membrane deformation function of epsin contributes to spindle organization during mitosis [46].As spindle matrix proteomics has revealed several endocytosis proteins [47,48], we believe that endocytic players, which were previously thought to be outside the spindles, may also switch to function in microtubule organization inside the spindles in a very complicated way [46]. Furthermore, quantitative phosphorproteomics suggests that some endocytic partners including clathrin are regulated by phosphorylation throughout the cell cycle [49,50], implicating that both kinases and phosphatases may coordinate the switch between endocytosis and mitosis through regulating phosphorylation state of endocytic regulators.…”
Section: Role Transitions Of Clathrin Between Endocytosis and Mitosismentioning
confidence: 99%